Riboflavin transporter deficiency: AAV9-SLC52A2 gene therapy as a new therapeutic strategy - Mei, Cecilia; Magliocca, Valentina; Chen, Xin; Massey, Keith; Gonzalez-Cordero, Anai; Gray, Steven J.; Tartaglia, Marco; Bertini, Enrico Silvio; Corti, Stefania; Compagnucci, Claudia (Frontiers in Cellular Neuroscience, 2025)
Riboflavin transporter deficiency syndrome (RTD) is a rare childhood-onset neurodegenerative disorder caused by mutations in SLC52A2 and SLC52A3 genes, encoding the riboflavin (RF) transporters hRFVT2 and hRFVT3. In the present study we focused on RTD Type 2, which is due to variants in SLC52A2 gene. There is no cure for RTD patients and, although studies have reported clinical improvements with administration of RF, an effective treatment is still unavailable. Here we tested gene augmentation therapy on RTD type 2 patient-derived motoneurons using an adeno-associated viral vector 2/9 (AAV9) carrying the human codon optimized SLC52A2 cDNA. We optimized the in vitro transduction of motoneurons using sialidase treatment. Treated RTD motoneurons showed a significant increase in neurite’s length when compared to untreated samples demonstrating that AAV9-SLC52A2 gene therapy can rescue RTD motoneurons. This leads the path towards in vivo studies offering a potential treatment for RTD patients.